Regionalizing eco-toxicity characterization factors for copper soil emissions considering edaphic information for Northern Spain and Portuguese vineyards - Villanueva-Rey, P. (2019)
The management of vineyards depends on the use of plant protection agents. Regardless of the numerous environmental impacts that these pesticides generate during their production, their dosage as pest control agents in vineyards causes an important toxic effect that must be monitored. Copper-based inorganic pesticides are the most widely used agents to control fungal diseases in humid wine-growing regions. It is, however, significant that the environmental analysis of their use through the Life Cycle Assessment (LCA) methodology does not provide detailed information on the potential toxicity of this type of pesticides. Hence, most studies report average values for copper characterization factors (CFs), excluding local soil characteristics. The objective of the study was the spatial characterization of the ecotoxicity factors of copper soil emissions as a function of the chemical characteristics of vineyard soils located in Portugal and Galicia (NW Spain). A multiple linear regression model was applied to calculate the comparative toxic potential. Subsequently, CFs for copper were calculated based on spatial differentiation considering the variable properties of the soil within each wine appellation. The CFs obtained for the area evaluated ranged from 141 to 5937 PAF·m3·day/kgCu emitted, for fibric histosols (HSf) and dystic cambisols (CMd), respectively. Moreover, the average values obtained for Galician and Portuguese soils were 1145 and 2274 PAF·m3·day/kgCu emitted, respectively. The results obtained illustrate the high variability of CF values as a function of the chemical characteristics of each type of soil. For example, Cu soil mobility was linked to organic carbon content and pH. Finally, to validate the representativeness of the calculated CFs, these were applied to the results of 12 literature life cycle inventories of grape production in the area evaluated, revealing that impact scores associated with Cu emissions can considerably vary when spatially-differentiated CFs are implemented.